3D printing of titanium alloy on selective laser melting systems - Bhandari, Chinmay (Nanyang Technological University, 2024)
Selective Laser Melting (SLM) is a method of metal additive manufacturing that falls under the category of Laser Power-Bed Fusion (L-PBF) technology. It has multiple advantages such as material versatility and the ability to print geometrically complex parts without additional machining. However, its surface quality and fatigue properties have been found to be inferior to conventional manufacturing methods. Process-related defects such as porosities, lack of fusion (LOF) and un-melted powders gives rise to areas of stress concentrations which leads to mechanical inferiority such as poor fatigue strength or toughness. This study aims to investigate and optimize the print process parameters for Ti-6Al-4V fabricated by SLM to reduce process-related defects and improve the mechanical strength of the material, with improved surface quality and microstructure. Layer height will be the main parameter being experimented with to find an optimum value for improved fatigue life, as it has a significant effect on defects in microstructure. Another reason to optimize layer height is to find suitable limits which can potentially save time to print which can usually take days, or even weeks. A total of 18 specimens, with layer heights of 30, 60 and 90 μm divided equally, were printed using SLM280 and subjected to fatigue tests according to ASTM standards. The fracture surface, especially the crack growth area, and surface quality were observed using optical microscopes, laser scanning microscopes and scanning electron microscopy. The findings of this study will contribute to the improvement of 3D-printed Ti-6Al-4V parts and have potential applications in the aerospace industry, where fatigue strength is a critical to strict safety standards.